Knowledge, attitude, and barriers toward polio immunization among pre-clinical students in Malaysia - Maung, Theingi Maung; Kulandaivalu, Shivenanthini; Xian, Chee Mei; Ramachandra, Kughan; Jai Devaraj, Sankari; Venkadason, Thiviyaa; Shirin, Lubna; Kabir, Mohammed Shahjahan (Asian Journal of Medical Sciences, 2021)
Background: Polio is reported as reemerging disease in Malaysia after 27 years of being free from it. It is important to identify the awareness towards polio vaccine among the medical students who are the future and the pillars of the nation, to develop a country. Aims and Objectives: This study aims to assess the knowledge, attitude, and barriers toward polio immunization among pre-clinical medical students. Materials and Methods: A cross-sectional study was conducted among 190 pre-clinical students from a private university after obtaining informed consent and institutional ethical clearance. Data collected from Google Forms questionnaire were analyzed using SPSS version 20. Results: Insufficient knowledge, especially on disease nature, transmission, and correct dosage of vaccine, was noticed. Findings revealed that 79.5% of the students showed unfavorable attitude toward polio immunization. Year 2 students are more positive toward the vaccination compared to year 1. Main barriers toward polio immunization selected by the respondents are disagreement from the spouse, insecure about vaccine safety, and distance of the health center. Conclusion: Pre-clinical students should enhance their knowledge to be able to recognize the various barriers of polio immunization in our country and be part of the effort in solving these barriers as polio eradication is critical to ensuring a healthier future for children.